Akuntabilitas Dana Desa Berbasis Kompetensi Aparatur Desa, Partisipasi Masyarakat, Pemanfaatan Teknologi Informasi dan Sistem Pengendalian Internal - Purwati Purwati (Akademi Akuntansi YKPN Yogyakarta, 2023)
Ensuring accountability in the management of village funds is crucial within village governance to enhance public trust in every program or activity conducted by the government for the benefit of the community. Challenges related to the mismanagement or misallocation of village funds by local authorities often stem from the inadequate competencies of village officials, limited involvement of the community in decision-making regarding village programs, and the absence of information technology infrastructure, including network instability, at the village offices across various villages. These elements are thought to influence the responsibility associated with overseeing village funds. This study aims to address two key questions: first, whether the competence of village officials, community engagement, and the adoption of information technology affect the accountability of village fund management; and second, to explore the accountability of village fund management from the standpoint of Islamic economics. The aim of this research is to is to investigate whether the competence of village officials, community involvement, and the utilization of information technology positively impact the accountability of village fund management, as well as to explore the level of accountability in village fund management. This research is a quantitative research where the population in this study was obtained from 12 villages with 110 respondents. The sampling technique used was purposive sampling. Data was obtained by documentation and questionnaires using multiple linear regression analysis. The results of this research show that Village Apparatus Competence, Community Participation, Use of Information Technology and Internal Control Systems each have a positive and significant effect on village fund accountability.